2013
DOI: 10.1080/10826068.2013.797435
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bacterial Cell Density and Recombinant Protein Yield Using a Commercial Microbial Cultivation System

Abstract: EnBase (BioSilta, Finland) is a microbial cultivation system that replicates fed-batch systems through sustained release of glucose by enzymatic degradation of a polymeric substrate. Achievable bacterial cell densities and recombinant capripoxvirus protein expression levels, solubility, and antigenicity using the EnBase system were assessed. BL21-AI Escherichia coli expressing capripoxvirus proteins achieved up to eightfold higher cell densities when grown in EnBase media compared with standard media. Greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These tablets are simply added to sterile water and dissolve in the first minutes of cultivation. Studies have shown that the technology can be easily combined with conventional approaches to yield not only higher amount of a target protein through the higher cell density [ 21 , 25 , 26 ], but also in many cases a higher amount of correctly folded protein per cell [ 26 , 27 ]. Modern screening systems, such as RAMOS, Biolector and PreSens’ SensorDish with an ability for on-line monitoring of growth data provide excellent tools to optimize the growth and expression conditions [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tablets are simply added to sterile water and dissolve in the first minutes of cultivation. Studies have shown that the technology can be easily combined with conventional approaches to yield not only higher amount of a target protein through the higher cell density [ 21 , 25 , 26 ], but also in many cases a higher amount of correctly folded protein per cell [ 26 , 27 ]. Modern screening systems, such as RAMOS, Biolector and PreSens’ SensorDish with an ability for on-line monitoring of growth data provide excellent tools to optimize the growth and expression conditions [ 28 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the final product yield is less independent on the time or cell density of induction [ 11 , 21 ]. For example, Peck et al [ 25 ] observed eight times higher cell densities and an increased protein yield per cell producing capripoxyvirus proteins which causes severe diseases in sheep and cattle. The production of Tissue-type plasminogen activators (t-PA) is commonly done in mammalian cell cultures.…”
Section: Introductionmentioning
confidence: 99%